Traktat Parkosza. Eksperymentalna edycja elektroniczna - Bień, Janusz S. (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The fifteenth-century Latin manuscript presenting the proposal of Polish spelling formulated by Jakub Parkosz is an interesting challenge to the editors primarily because it introduces special characters that were not used later. The text of the treatise was presented and discussed in a book by Marian Kucała (available under open licence) which was used as the basis for an experimental electronic edition of the treatise in the form of an interactive PDF file, also available as a LuaLaTeX source. For transliteration, the electronic edition uses the existing Unicode letters with some additions from the private use area of the Medieval Unicode Font Initiative. This paper presents the rationale for the transliteration and discusses some possible alternative forms of electronic editions.